Reducing firearm violence: a research agenda - Weiner, Janet (BMJ Group, 2007)
In the United States, firearms are involved in tens of thousands of deaths and injuries each year. The magnitude of this problem prompted the National Academy of Sciences (NAS) to issue a report in 2004 detailing the strengths and limitations of existing research on the relationship between firearms and violence. In response, a multidisciplinary group of experts in the field of firearms and violence formed the National Research Collaborative on Firearm Violence. The Collaborative met for 2 days in June 2005 to (1) critically review the main findings of the NAS report and (2) define a research agenda that could fill research and data gaps and inform policy that reduces gun-related crime, deaths and injuries. This article summarizes the Collaborative's conclusions and identifies priorities for research and funding.